Chemical Constituents of Thymus eriocalyx Leaves of Iranian Origin Plant - HADI MESHKATALSADAT, MOHAMMAD; SADEGHI SARABI, REZA; MOHARAMIPOUR, SAEID (Asian Journal of Chemistry, 2010)
The chemical composition of the volatile oil of the fresh leaves of Thymus eriocalyx growing wild in Lorestan state of Iran was analyzed by gas chromatography-mass spectrometry. Fifteen compounds consisting of 98.77% of the oil were identified. The major constituents identified were 1,8-cinole (3.07%), L-linalool (1.01%), thymol (66.34%), caryophyllene oxide (2.96%) and carvacrol (7.5%).